HIGHER EDUCATIONAL INSTITUTIONS AS A CENTER OF INNOVATIVE ACTIVITY IN REGIONS - Noskov A.А. (Perm Federal Research Centre Journal, 2016)
This article focuses on the identification of problems in the Russian innovation system and the role of higher education institutions in innovation activity of a region.